Safety analysis of safety-critical systems for their applicability on NPP systems: A state-of-the-art review - Kumar V.; Maurya A.K.; Singh K.V.; Singh L.K.; Singh P.; Hati A.N.; Singh V.P. (My University, 2025)
Since any risk in the safety-critical systems (SCSs) might lead to a terrible disaster, the utmost quality attribute of these systems is safety. Researchers are putting their efforts to ensure the safety of such systems. This paper summarizes the state-of-the-art in the area of the safety attribute of such critical systems. The in depth literature survey is performed to explore the several methods/models used for safety analysis of the SCS. The limitations of such methods are also shown regarding their applicability in SCS of the nuclear power plant (NPP). We also propose a framework to perform safety analysis, which can deal with these limitations and demonstrated the approach on a case study of NPP. Further, the direction for future work is advised to extend the further scope of research based on the case study. © 2021 John Wiley & Sons Ltd.